Pengaruh Kepemimpinan, Insentif, dan Motivasi Pada Kinerja Pegawai Bidang Akuntansi (Studi Pada Pemerintah Kabupaten Buleleng) - Manubawa, Ida Bagus Gde Adi; Novitasari, I Gusti Ayu; Masari, Ni Made Galih (Penerbit Goodwood, 2025)
Purpose: This investigate looks for to look at the affect of authority, motivations, and inspiration on the execution of bookkeeping staff within the Government of Buleleng Rule. Methodology: The inquire about utilizes a quantitative approach utilizing nonprobability examining, particularly purposive examining. The information were gotten through surveys disseminated to 40 bookkeeping workers over different Territorial Government Organizations (OPD) in Buleleng Rule. The collected information were at that point analyzed utilizing numerous straight relapse with the help of SPSS adaptation 25 computer program. Result: The discoveries of the ponder demonstrate that authority, motivating forces, and inspiration have a positive and noteworthy affect on worker execution, both independently and at the same time. This demonstrates that good leadership, appropriate incentive schemes, and high motivation contribute to increased employee productivity and performance. Limitations: Be that as it may, the think about isn't without restrictions, because it is based on a generally little test measure and its center on a single rule. Contribution: In any case, the study's discoveries offer important commitments to the spaces of bookkeeping, human resource management, and public administration, particularly in the context of enhancing government employee management strategies. Moreover, the research serves as a valuable reference for local governments in formulating policies aimed at enhancing employee performance through the implementation of effective leadership, appropriate incentives, and motivation.